Contributions of mangrove conservation and restoration to climate change mitigation in Indonesia - Virni Budi Arifanti; John Boone Kauffman; Subarno; Muhammad Ilman; Anna Tosiani; Nisa Novita (Global Change Biology, 2022)
Mangrove forests are important carbon sinks, and this is especially true for Indonesia where about 24% of the world's mangroves exist. Unfortunately, vast expanses of these mangroves have been deforested, degraded or converted to other uses resulting in significant greenhouse gas emissions. The objective of this study was to quantify the climate change mitigation potential of mangrove conservation and restoration in Indonesia. We calculated the emission factors from the dominant land uses in mangroves, determined mangrove deforestation rates and quantified the total emissions and the potential emission reductions that could be achieved from mangrove conservation and restoration. Based on our analysis of the carbon stocks and emissions from land use in mangroves we found: (1) Indonesia's mangrove ecosystem carbon stocks are among the highest of any tropical forest type; (2) mangrove deforestation results in greenhouse gas emissions that far exceed that of upland tropical deforestation; (3) in the last decade the rates of deforestation in Indonesian mangroves have remained high; and (4) conservation and restoration of mangroves promise to sequester significant quantities of carbon. While mangroves comprise only ≈2.6% of Indonesia's total forest area, their degradation and deforestation accounted for ≈10% of total greenhouse gas emissions arising from the forestry sector. The large source of greenhouse gas emissions from a relatively small proportion of the forest area underscores the value for inclusion of mangroves as a natural climate solution. Mangrove conservation is far more effective than mangrove restoration in carbon emissions reductions and an efficient pathway to achieve Indonesia's nationally determined contribution (NDC) targets. The potential emission reduction from halting deforestation of primary and secondary mangroves coupled with restoration activities could result in an emission reduction equivalent to 8% of Indonesia's 2030 NDC emission reduction targets from the forestry sector.